A computer model of the distribution of the tapeworm Echinococcus multilocularis in Ukraine - Tytar, V.M.; Kozynenko, I.I. (Доповіді НАН України, 2024)
Alveolar echinococcosis, caused by the larval form of the parasitic tapeworm Echinococcus multilocularis, affects a wide range of animal species, including domestic and wild livestock, and is a highly pathogenic helminthic disease for humans. Recently developed for the species habitat suitability maps are restricted to the border of the European Union and have left Ukraine outside the scope of this study. Our goal was to model and characterize the large-scale ecological niche of E. multilocularis in Europe, placing a particular emphasis on Ukraine, and to justify an assessment of the risk of E. multilocularis transmission in Ukraine under current environmental conditions. Using the CMCC-BioClimInd dataset and a Bayesian modeling approach, we developed a habitat suitability map for the species in Ukraine and distinguished corresponding risk areas. We anticipate the model will enhance future surveillance eff orts and help to understand the epidemiological situation of the disease, especially under wartime conditions.